2020
DOI: 10.3390/nu12020279
|View full text |Cite
|
Sign up to set email alerts
|

Salt and Health: Survey on Knowledge and Salt Intake Related Behaviour in Italy

Abstract: Background and aim: Excess sodium intake is a recognised causal factor of hypertension and its cardiovascular complications; there is however a lack of practical instruments to assess and monitor the level of knowledge and behaviour about dietary salt intake and to relate these factors to the population general dietary habits. Methods and Results: A self-administered questionnaire was developed to assess the salt and health related knowledge and behaviour of the Italian population through an online survey. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 34 publications
3
30
0
2
Order By: Relevance
“…Considering that about 10% of the total salt intake is provided by the small amounts of salt contained in natural foods, only 35% of the total salt intake of Italian households is discretionary (salt added to foods while cooking or at the table). In an online survey of an opportunistic sample of Italian adult population ( n = 11618) carried out in 2016–2018 [ 39 ], only 50% of the participants declared use of iodized salt on a regular basis, suggesting little change from previously published data in this regard [ 16 ]. Accordingly, the National Institute of Health Surveillance PASSI (Progress of the Health Authorities for Health in Italy) report indicated that, whereas 71% of a large sample of adult population declare the use of iodized salt, 53% stated to use it on a regular basis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that about 10% of the total salt intake is provided by the small amounts of salt contained in natural foods, only 35% of the total salt intake of Italian households is discretionary (salt added to foods while cooking or at the table). In an online survey of an opportunistic sample of Italian adult population ( n = 11618) carried out in 2016–2018 [ 39 ], only 50% of the participants declared use of iodized salt on a regular basis, suggesting little change from previously published data in this regard [ 16 ]. Accordingly, the National Institute of Health Surveillance PASSI (Progress of the Health Authorities for Health in Italy) report indicated that, whereas 71% of a large sample of adult population declare the use of iodized salt, 53% stated to use it on a regular basis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Females and better-educated people were more likely to have higher levels of saltrelated knowledge, and they were more interested in and more active in salt reduction [21,25,33,48]. In this study, it was also found that in both 2019 and 2020, higher education levels came with higher scores of salt-related knowledge and salt reduction behaviors; females had higher salt-related knowledge scores and relatively lower high-salt intake behavior scores, but the salt reduction behavior score did not differ by gender.…”
Section: Discussionmentioning
confidence: 99%
“…Education on salt-related knowledge and how to reduce salt intake could reduce 24 h urinary sodium of children and their families from the School-EduSalt study, and better diet-related knowledge, attitudes and behaviors were associated with higher health status [16,20]. However, behavior change is complex, long-term and slow; understanding the current population statuses of salt-related knowledge, attitudes and behaviors are essential for further salt-reduction actions [21], and similar studies had been conducted in Australia, America and other countries [22][23][24][25][26]. Salt-related knowledge and behaviors of Chinese residents in 2015 were explored in a previous study [27], based on the data of data from the China Chronic Diseases and Nutrition Surveillance system, and low awareness rate of maximum daily salt intake and the behavior rate of salt reduction of Chinese adult residents were found.…”
Section: Introductionmentioning
confidence: 87%
“…Based on the total salt consumption results and on the estimate by Leclercq and coworkers of a 35% discretionary salt intake in Italy [ 23 ], we estimate that discretionary salt consumption in our study population was approximately 4.3 g/day for men and 3.3 g/day for women, which is quite high with respect to the WHO recommendation of a 5-g total daily salt intake. It must be noticed that the results of an online survey conducted by the Italian Society of Human Nutrition (SINU) Group on an opportunistic sample of Italian general population indicated that the proportion of people who declare the regular use of iodized salt in the preparation and consumption of food at home (“discretionary” salt) may indeed not exceed 50% [ 24 ]. Approximately in the same period (2016–2019), another survey within the PASSI surveillance system of the National Institute of Health on 130,000 subjects showed that 41% of the people interviewed declare to use iodized salt “always”, 12% “often” and 18% sometimes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%